2016
DOI: 10.1186/s12907-016-0039-3
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid extraction from formalin-fixed paraffin-embedded cancer cell line samples: a trade off between quantity and quality?

Abstract: BackgroundAdvanced genomic techniques such as Next-Generation-Sequencing (NGS) and gene expression profiling, including NanoString, are vital for the development of personalised medicines, as they enable molecular disease classification. This has become increasingly important in the treatment of cancer, aiding patient selection. However, it requires efficient nucleic acid extraction often from formalin-fixed paraffin-embedded tissue (FFPE).MethodsHere we provide a comparison of several commercially available m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…The quality control of isolated RNA (Boeckx et al, 2011;Ludyga et al, 2012;Seiler et al, 2016) from all the tissue samples in this study showed RNA integrity numbers (RIN) ≥1.9. The FFPE tissue samples ranged from 1.9 to 2-6 while the RIN of FF tissue samples ranged from 2 to 8.5.…”
Section: Discussionmentioning
confidence: 79%
“…The quality control of isolated RNA (Boeckx et al, 2011;Ludyga et al, 2012;Seiler et al, 2016) from all the tissue samples in this study showed RNA integrity numbers (RIN) ≥1.9. The FFPE tissue samples ranged from 1.9 to 2-6 while the RIN of FF tissue samples ranged from 2 to 8.5.…”
Section: Discussionmentioning
confidence: 79%
“…Formalin-fixed paraffin-embedded (FFPE) samples represent a valuable under-exploited resource for large, retrospective and prospective studies with long-term clinical follow-up [1]. The existence of FFPE samples collections worldwide, and their advantages such as easy handling, long-term inexpensive storage, suitability for immunohistochemical analyses, and low-cost of large-scale application, make this type of storage a relevant option [2].…”
mentioning
confidence: 99%
“…Variation in RNA quality results in inaccurate and misleading changes in molecular profiling, underpinning the need for reliable and reproducible protocols for the processing of tissue and extraction of RNA [10]. Numerous studies have compared extraction kits for the isolation of nucleic acids from FFPE tissue, with key factors to consider listed for researchers prior to undertaking experimental processes [1,11]. While DNA/RNA Shield yielded similar quality scores to RNA extracted from FFPE tissue, there was substantial variation in the total yield of RNA.…”
Section: Discussionmentioning
confidence: 99%